Celestica to acquire MSL (PR Newswire, 2003)
Under the transaction, each outstanding common share of MSL will be exchanged for 0.375 subordinate voting shares of Celestica. In addition, the holders of Series A and Series B preferred shares of MSL will be entitled to receive, at the shareholder's election, US$52.50 per share plus accrued dividends in cash or a number of subordinate voting shares of Celestica equal to 0.375 times the number of common shares of MSL into which the Series A and Series B shares may be converted (plus, in the case of the Series B preferred shares, a "make-whole" payment of US$2.25 per share payable in either cash or shares at the option of MSL). The share exchange ratio will be adjusted, if necessary, to ensure that the value of the consideration received for each MSL common share (based on the 20 trading day volume weighted average NYSE closing price of the subordinate voting shares of Celestica determined on the third business day prior to the completion of the transaction) will be not less than US$6.00 and not more than US$7.25. MSL has approximately 34,398,030 common shares and 1,330,000 Series A and B preferred shares outstanding. The merger agreement, which has been approved unanimously by the boards of directors of MSL and Celestica, is subject to MSL shareholder approval and certain governmental consents. Certain institutional shareholders of MSL and officers of MSL, holding shares representing approximately 41.5% of the votes to be cast on the merger, have entered into unconditional agreements to vote in favour of the merger, and the institutional shareholders have also granted Celestica the option to acquire from them, under certain circumstances, MSL shares representing 30% of the votes that can be cast in connection with the merger. All parties have agreed to proceed expeditiously to close the transaction. "I look forward to the combined strength of the Celestica/MSL organization. As a respected EMS provider with a broad customer base in diversified end markets such as industrial and avionics, MSL has an excellent track record for delivering the highest standards of service. MSL's customer- focused approach based on focus and flexibility is highly compatible with that of Celestica," said Eugene Polistuk, Celestica's chairman and chief executive officer. "This acquisition also supports Celestica's strategy to continue to expand and deepen its suite of integrated services and solutions. MSL's strengths in order fulfillment, build-to-order assembly and high-speed automated manufacturing complement our current offerings. I am confident that the combined organization will create additional value for our respective customers."